Immunodepression in trypanosome-infected mice. VI. Comparison of immune responses of different lymphoid organs - Kar, S.K.; Roelants, G.E.; Mayor-Withey, K.S.; Pearson, T.W. (Wiley, 1981)
Mitogen stimulation of cells from various lymphoid organs of C3H/He mice chronically infected with an isolate of Trypanosoma congolense was studied at different time intervals after infection, using concanavalin A (Con A) and lipopolysaccharide (LPS). At the same time, changes in the percentages of T, B and null lymphocytes in these organs were determined by immunofluorescence staining. The responses of T and B lymphocytes in the spleen were totally depressed, and the cellular composition was drastically altered by day 14 after infection. Unlike the spleen, the lymph nodes showed minor changes in their T and B lymphocyte responses and cell composition during the course of the infection, except the B cell response and composition which were altered late in the infection. The thymus and bone marrow did not show any appreciable changes in their mitogen responses and cell composition throughout the infection. The peripheral blood lymphocytes showed reduced B cell responses. Spleen cells from chronically infected mice suppressed lymphocyte stimulation induced in normal spleen and lymph node cell populations by Con A, LPS and allogeneic stimulator cells. Lymph node cells from the same group of mice did not exhibit any such suppressor activity.In the experimental system used here, the spleen is the primary site of immune depression, and other lymphoid organs such as the lymph nodes and thymus are very little affected.